The Influence of some Factors of Social Environment on the Stature of School Children in Poland - Jedlińska, Wanda (Anthropological Review, 1985)
The social environment has been characterized by three factors: degree of urbanization, parents education and family size. The effect of these factors on the stature was investigated by the method of homogeneous groups and the method of variation analysis. There is a distinct influence of social factors on the body height of children. It is possible to indicate social groups discriminated regarding the socio-economic status.